Pengaruh Attachment terhadap Self-Disclosure pada Pria Dewasa Awal yang Berpacaran - Helen Xaveria Pangestu; Jessica Ariela (Universitas Kristen Maranatha, 2020)
Dating is a stage for human to create bonds with the opposite sex which is generally in early adulthood. Conflict is unavoidable in dating relationship and this issue often relates to communication problems. Self-disclosure is considered to be one way to minimize conflict. A person who feels safe and secure in building attachment, tend to self-disclose more often and to communicate directly rather than those who feel insecure. This study aims to study whether attachment, which consists of two dimensions – anxiety and avoidance, have an effect on self-disclosure on 72 male young adults who are currently in dating relationship. This study is a quantitative study using Experiences in Close Relationships-Revised Scale and Revised Self-Disclosure Scale as instruments of research. The result indicates that there are negative influences between attachment anxiety toward self-disclosure (R2=.09, F= 7.127, p<.05) and attachment avoidance toward self-disclosure (R2=.22, F= 20.258, p<.05). This means, the higher the level of someone’s attachment anxiety and/or attachment avoidance, self-disclosure will be lower, and vice versa. However, when counted together as a construct, only attachment avoidance showed significant effect on self-disclosure. Other findings related to attachment and self-disclosure are also discussed. Keywords: attachment, self-disclosure, dating relationship, early adulthood